By evening's light [large type] - Gould, Leslie, 1962- (Gould, Leslie, 1962- Amish memories, 2024)
"Treva Zimmerman finds herself at a crossroads in life after a heartbreaking failed relationship. Returning to Lancaster County to visit her Amish grandparents and elderly aunt, Treva plans to leave her Plain heritage behind for a fresh start in Alaska. Torn between the expectations of her community and her own desires, she seeks to follow her own path -- but all that changes when her aunt Rosene suffers a heart attack. As her aunt recounts her own past -- a poignant journey through Cold War Germany and a fervent desire to escape her Plain life to search for a lost love -- Treva is determined to discover the whereabouts of Rosene's former sweetheart. Amid the turmoil, their former farmhand Gabe Johnson returns unexpectedly, throwing Treva's plans into further disarray. While working hard to save the farm and explore her own destiny, Treva confronts her deep-rooted ties to her heritage and must decide if she will embrace her family's legacy or break free from the pressures of her past to forge a life of her own."--